Phenomenology as an interpretive frame: The evolution of a research method for understanding how learning is experienced in collaborative inquiry groups - thINQ (Adult Education Research Conference, 1994)
To make meaning of a three-year study of collaborative inquiry, thINQ, a group of five doctoral candidates, adopts phenomenology as an interpretive frame and discovers phenomenology-in-five-voices and collaborative phenomenology.